(untitled) (Al-Qamar, 2024)
The current research article gives a detailed analysis of the topic of the WTO’s DSM by exploring the trends, challenges, and prospects of the DSM. The evolution process of the DSM is discussed with regard to the prominent trends explaining the gradual transformation of the instrument in the course of the global trade evolution. To that end, the article goes deep into exploring different difficulties that the DSM is currently experiencing, namely, the Appellate Body crisis, an increase in the time it takes to solve disputes and compliance. Specific measures that have been proposed are called into question, which relate to the reform of the Appellate Body, curbing backlog issues, and increasing the transparency of DSM actions. Evolutions of the selected trends are evident in the analysis of attempts to improve the DSM in line with modern trade conflict realities. Another frequent topic discussed in the course of the research can be named as transparency issues of DSM proceedings. This article covers several aspects important for openness, namely documents’ availability, open and clear hearings, advanced notification, and clear statement of the decision made. Such transparency-boosting measures are in consonance with the endeavor of the WTO to become more responsible and inclusive in resolving disputes. Thus, the identification of an independent review mechanism and learning programs targeting the actors involved in capacity-building provide additional grounds for the evolution of the DSM. Thus, this research article sums up the tendencies, threats, and opportunities that define the development of the WTO DSM. This way, the article outlined challenges that need to be resolved and opportunities offered by suggested reforms to consolidate a more effective DSM which will continue to address the intricacies of global trade while maintaining the efficiency of the multilateral trading system.